(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Formative assessment has become one of the most powerful drivers of progress in English language teaching (ELT) because it makes learning visible while it is still in progress. Unlike summative assessment, which judges achievement at the end of a unit, formative assessment supports learners during learning through timely feedback, clear success criteria, and purposeful adjustments to instruction. This article explains the concept and key principles of formative assessment in ELT, demonstrates practical classroom techniques for assessing speaking, listening, reading, and writing, and discusses how formative assessment improves motivation, autonomy, and measurable learning outcomes. It also addresses common challenges—large classes, time limitations, exam pressure, and reliability—and offers realistic solutions. The article concludes that effective formative assessment is not an additional burden but a teaching mindset: eliciting evidence of learning, interpreting it accurately, and acting on it to move learners forward.